Book Review: Archaeology and Urban Settlement in Late Roman and Byzantine Anatolia: Euchaïta-Avkat- Beyözü and its Environment, eds. J. HALDON, H. ELTON and J. NEWHARD, Cambridge University Press 2018 - KARAGIORGOU, Olga (Byzantina Symmeikta, 2020)
Archaeology and Urban Settlement in Late Roman and Byzantine Anatolia: Euchaïta-Avkat- Beyözü and its Environment, eds. John Haldon, Hugh Elton and James Newhard, Cambridge University Press 2018